ISLAMIC EDUCATION GENEALOGY AS THE BASIS OF TREATING RELIGIOUS PLURALISM AND RELIGIOUS COMMUNITY HARMONY - Hasan Bisri (Universitas Islam Malang, 2023)
This article discusses multicultural education as a relevant educational model used as a basis for caring for religious pluralism and religious harmony for the people of Karangpandan Village who have religious diversity. The background of this study is that there are many groups of intellect towards religious pluralism which ultimately distort national unity. Seeing these conditions, it is important to make real efforts in order to re-awaken the importance of religious pluralism and religious harmony. This study uses a qualitative approach with ethnographic types. The main objective of this research is to describe religious diversity, religious pluralism, and religious harmony and to treat religious pluralism and religious harmony in Karangpandan Village that is obtained from empirical data. To obtain a valid data, it is done by means of participant observation, in-depth interviews, and document analysis. Data sources were selected using a snowball sampling pattern, while the analysis was based on qualitative data/informants in the field using four types of qualitative data analysis techniques, namely domain analysis, taxonomy, componential analysis, and cultural theme analysis. The results of this study indicate that the formal findings of this research is the collaborative accommodative multicultural Islamic education model, that is, a plural society that has a dominant culture, makes certain adjustments and accommodations for the cultural needs of minorities, formulates and implements culturally sensitive laws, and provides freedom to minorities to maintain and develop their culture, otherwise the majority do not against the dominant culture and between the majority and minority groups collaborate to build and maintain a culture of society that implements the values ​​of multicultural education. Keywords: : Genealogy of Islamic Education, Religious Pluralism,